PENGARUH STRATEGI PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT TERHADAP PEMAHAMAN KONSEP DAN SIKAP PEDULI LINGKUNGAN SISWA KELAS VII MTSN 2 BONDOWOSO - Khairin Nisaq; Dinar Maftukh Fajar (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
The preliminary study of this research has found that science learning in MTsN 2 Bondowoso, East Java had the following issues: the average student score for science subjects was still relatively low, student learning activity in the classroom still needed more improvement, and some students had a low environmental care attitude. This was observed from the amount of rubbish still found under the table and according to interviews the students did not yet know how to process the waste. The purpose of this study is to find out the differences of Science, Technology, and Society learning strategy on the conceptual understanding and environmental care attitude for students of grade VII MTsN 2 Bondowoso. This research belonged to a quasi-experimental type with the Nonequivalent Control Group Design. The sample involved consisted of 56 students whom were grouped into the experimental and the control class. The hypothesis test used was t test (independent sample t-test). The data collection techniques used were questionnaires for environmental care attitude, interviews, observations, and tests. From the results of hypothesis testing, it obtained t value for students' conceptual understanding of 8.30 and t table of 2.04, and t value for students' environmental care attitude of 4.62 and t table of 2.04 with a 5% significant level. This showed a significant difference in the average score of students' conceptual understanding and students' environmental care attitude before and after implementing the Science, Technology, and Society learning strategy.